Challenges for monetary policy - Otmar Issing (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
The financial crisis which started in 2007 has caused a tremendous challenge for monetary policy. The simple concept of inflation targeting has lost its position as state of the art. There is a debate on whether the mandate of a central bank should not be widened. And, indeed, monetary policy has been very accommodative in the last couple of years and central banks have modified their communication strategies by introducing forward guidance as a new policy tool. This paper addresses the consequences of these developments for the credibility, the reputation and the independence of central banks. It also comments on the recent debate among economists concerning the question whether the ECB's OMT program is compatible with its mandate.
urn:nbn:de:hebis:30:3-322799
Keywords: 330; ECB; OMT; central banking